Swap70b is required for convergent and extension cell movement during zebrafish gastrulation linking Wnt11 signalling and RhoA effector function - Xu, Xiaoou; Shuen, Wai Ho; Chen, Chen; Goudevenou, Katerina; Jones, Peter; Sablitzky, Fred (Elsevier, 2014)
Swap70 functions as a guanine nucleotide exchange factor for Rac and RhoA regulating F-actin cytoskeletal rearrangements and playing a crucial role in mammalian cell activation, migration, adhesion and invasion. Here we show that the zebrafish orthologue, Swap70b, is required for convergent and extension cell movement during gastrulation. Swap70b morphants exhibited broader and shorter body axis but cell fate specification appeared normal. While ectopic Swap70b expression robustly rescued Wnt11 morphants, RhoA overexpression was sufficient to rescue Swap70b morphants, establishing Swap70b as a novel member of the non-canonical Wnt/PCP pathway downstream of Wnt11 and upstream of RhoA. This is distinct from the related Def6a protein that acts downstream of Wnt5b. Def6a/Swap70b morphants resemble Ppt/Slb double mutant embryos suggesting that Swap70b and Def6a delineate Wnt11 and Wnt5b signalling pathways.